Response of novel insecticides in enhancing the productivity of lac on Flemingia semialata - JAISWAL, A K; SINGH, J P (The Indian Journal of Agricultural Sciences, 2020)
The field experiment was conducted to evaluate the impact of some selected new insecticides in enhancing the lac productivity by containing the incidence of lac insect predators on Flemingia semialata during 2014-15, 2015- 16 and 2016-17 at the Research Farm of ICAR-Indian Institute of Natural Resins and Gums, Ranchi, Jharkhand, India. Application of emamectin benzoate on kusmi-winter lac crop showed 4.57-157.14, 27.28- 322.73 and 69.56- 339.12% increase in sticklac yield for one, two and three sprays, respectively, at different concentrations. Two spray of emamectin benzoate (25-30 and 38-40 days of inoculation) at 0.0025% caused 322.73% increase in sticklac yield over control. Similarly, application of chlorantraniliprole increased the yield to the tune of 5.56-61.33, 10.76-248.10 and 22.0-333.33%, respectively, for one, two and three sprays (25-30, 38-40 and 60-65 days of inoculation). Three sprays of 0.01% chlorantraniliprole results 333.33% increase in yield over control. The visible impact of novaluron on sticklac yield is not manifested. Earlier these insecticides have been evaluated for their response on population of lac associated insect fauna but this is first evaluation study for assessing their impact on sticklac productivity.